3D stereolithography printing of graphene oxide reinforced complex architectures. (7th October 2015) - Lin, Dong; Jin, Shengyu; Zhang, Feng; Wang, Chao; Wang, Yiqian; Zhou, Chi; Cheng, Gary J
Abstract: Properties of polymer based nanocomposites reply on distribution, concentration, geometry and property of nanofillers in polymer matrix. Increasing the concentration of carbon based nanomaterials, such as CNTs, in polymer matrix often results in stronger but more brittle material. Here, we demonstrated the first three-dimensional (3D) printed graphene oxide complex structures by stereolithography with good combination of strength and ductility. With only 0.2% GOs, the tensile strength is increased by 62.2% and elongation increased by 12.8%. Transmission electron microscope results show that the GOs were randomly aligned in the cross section of polymer. We investigated the strengthening mechanism of the 3D printed structure in terms of tensile strength and Young's modulus. It is found that an increase in ductility of the 3D printed nanocomposites is related to increase in crystallinity of GOs reinforced polymer. Compression test of 3D GOs structure reveals the metal-like failure model of GOs nanocomposites.